RNA binding activity of heterodimeric splicing factor U2AF: at least one RS domain is required for high-affinity binding. - Rudner, D.Z.; Breger, K.S.; Kanaar, R.; Adams, M.D.; Rio, D.C. (Molecular and Cellular Biology, 1998)
The pre-mRNA splicing factor U2AF (U2 small nuclear ribonucleoprotein particle [snRNP] auxiliary factor) plays a critical role in 3' splice site selection. U2AF binds site specifically to the intron pyrimidine tract between the branchpoint and the 3' splice site and targets U2 snRNP to the branch site at an early step in spliceosome assembly. Human U2AF is a heterodimer composed of large (hU2AF65) and small (hU2AF35) subunits. hU2AF65 contains an arginine-serine-rich (RS) domain and three RNA recognition motifs (RRMs). hU2AF35 has a degenerate RRM and a carboxyl-terminal RS domain. Genetic studies have recently shown that the RS domains on the Drosophila U2AF subunit homologs are each inessential and might have redundant functions in vivo. The site-specific pyrimidine tract binding activity of the U2AF heterodimer has previously been assigned to hU2AF65. While the requirement for the three RRMs on hU2AF65 is firmly established, a role for the large-subunit RS domain in RNA binding remains unresolved. We have analyzed the RNA binding activity of the U2AF heterodimer in vitro. When the Drosophila small-subunit homolog (dU2AF38) was complexed with the large-subunit (dU2AF50) pyrimidine tract, RNA binding activity increased 20-fold over that of free dU2AF50. We detected a similar increase in RNA binding activity when we compared the human U2AF heterodimer and hU2AF65. Surprisingly, the RS domain on dU2AF38 was necessary for the increased binding activity of the dU2AF heterodimer. In addition, removal of the RS domain from the Drosophila large-subunit monomer (dU2AF50DeltaRS) severely impaired its binding activity. However, if the dU2AF38 RS domain was supplied in a complex with dU2AF50DeltaRS, high-affinity binding was restored. These results suggest that the presence of one RS domain of U2AF, on either the large or small subunit, promotes high-affinity pyrimidine tract RNA binding activity, consistent with redundant roles for the U2AF RS domains in vivo.